Hypoxia-Inducible Ubiquitin Specific Peptidase 13 Contributes to Tumor Growth and Metastasis via Enhancing the Toll-Like Receptor 4/Myeloid Differentiation Primary Response Gene 88/Nuclear Factor-κB Pathway in Hepatocellular Carcinoma - Gao, Shan; Chen, Tianxiang; Li, Lijie; Liu, Xin; Liu, Yang; Zhao, Junjun; Lu, Qiliang; Zeng, Zhi; Xu, Qiuran; Huang, Dongsheng; Tu, Kangsheng (Frontiers in Cell and Developmental Biology, 2020)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death worldwide. Activation of the toll-like receptor 4 /myeloid differentiation primary response gene 88/nuclear factor-κB (TLR4/MyD88/NF-κB) pathway contributes to the development and progression of HCC. The ubiquitin-proteasome system regulates TLR4 expression. However, whether ubiquitin specific peptidase 13 (USP13) stabilizes TLR4 and facilitates HCC progression remains unclear. Here, qRT-PCR and immunohistochemistry analysis revealed that USP13 expression in HCC tissues was higher than in nontumor liver tissues. Moreover, the elevated expression of USP13 was detected in HCC cells (SK-HEP-1, HepG2, Huh7, and Hep3B) compared to LO2 cells. Interestingly, the positive staining of USP13 was closely correlated tumor size ≥ 5 cm and advanced tumor stage and conferred to significantly lower survival of HCC patients. Next, USP13 knockdown prominently reduced the proliferation, epithelial-mesenchymal transition (EMT), migration, and invasion of Hep3B and Huh7 cells, while USP13 overexpression enhanced these biological behaviors of HepG2 and LO2 cells. The silencing of USP13 significantly restrained the growth and lung metastasis of HCC cells in vivo. Mechanistically, the USP13 depletion markedly inhibited the TLR4/MyD88/NF-κB pathway in HCC cells. USP13 interacted with TLR4 and inhibited the ubiquitin-mediated degradation of TLR4. Significantly, TLR4 re-expression remarkably reversed the effects of USP13 knockdown on HCC cells. USP13 expression was markedly upregulated in HCC cells under hypoxia conditions. Notably, USP13 knockdown repressed hypoxia-induced activation of the TLR4/MyD88/NF-κB pathway in HCC cells. In conclusion, our study uncovered that hypoxia-induced USP13 facilitated HCC progression via enhancing TLR4 deubiquitination and subsequently activating the TLR4/MyD88/NF-κB pathway.